MODULAR SYSTOLIC DIGITAL SIGNAL PROCESSOR WITH RECONFIGURING THE STRUCTURE - Igor Anatol’evich Kalmykov; Artem Bronislavovich Sarkisov; Ekaterina Mihaylovna Yakovleva; Maksim Igorevich Kalmikov (Вестник Северо-Кавказского федерального университета)
Computational systolic model for orthogonal signal transformation in extended Galois GF(pv) fields based on polynomial system of residue classes is examined. Modular codes' ability to increase fault-tolerant characteristics is proven.